RELATION BETWEEN SMOKING AND MICROALBUMINURIA - Dr. A. BHAGYALAKSHMI; Dr. CH. ANITHA; Dr. Md. DAWOOD SULEMAN (International Journal of Pharma and Bio Sciences, 2016)
Smoking increases the risk of renal disease and progresses to end stage renal disease. We therefore performed a population based study at Gandhi Medical College/Gandhi Hospital, Secunderabad in which we studied the relation between smoking and urinary albumin excretion. Smokers had a higher urinary albumin excretion (Albumin excretion 384 ± 12.8 mg / day: P<0.01) than those who do not smoke. In conclusion smoking is associated with albuminuria.